INTERACTIVE TEACHING METHODS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the importance of interactive teaching methods in higher pedagogical education, using the teaching of Russian language and literature as an example. It examines the specific features of interactive interaction in the educational process and its impact on the development of professional competencies in future philology teachers. The most effective forms and methods of interactive teaching, which contribute to the development of students' cognitive activity, communication skills, and independent thinking, are analyzed. The need for the systematic implementation of interactive technologies in the educational practices of pedagogical institutes is substantiated.